Search 74,310 tutors
FIND TUTORS
Ask a question
0 0

-x^2+70x-600=0

Tutors, please sign in to answer this question.

2 Answers

Multiply both sides of the equation by -1. You get the following equation:
 
x^2 - 70x + 600 = 0
 
Factor the quadratic equation. You get: 
 
(x - 60)(x - 10) = 0
 
x - 60 = 0
 
x = 60
 
x - 10 = 0
 
x = 10
Agree with Muhammad
 
you could also use the equation
 
x = (-b ± sqrt(b2-4*a*c)/(2*a)
 

-x^2+70x-600
ax^2+bx+c
 
a = -1
b = 70
c = -600
 
x = (-b ± sqrt(b^2-4*a*c)/(2*a) = (-70 ± sqrt(70^2-4*(-1)*(-600))/(2*(-1))
 
x = (-70 ± sqrt(4900-2400)/(-2)
 
x = (-70 ± sqrt(2500)/(-2)
 
x = (-70 ± 50)/(-2)
 
x = (-70 + 50)/(-2)  or    x = (-70 - 50)/(-2)
 
x = (-20)/(-2) or x = (-120)/(-2)
 
x = 10 or x = 60

Seattle Quadratic Equations tutors